The Bcl-2 family - Huang, David (Henry Stewart Talks, 2007)
Apoptosis, Discovery of Bcl-2, Cell death in worms, Evolutionarily conserved pathways to cell death, How cell death initiates, BH3-only proteins, Control of BH3- only proteins, Promiscuous and selective BH3-only proteins, Diverse Bcl-2 prosurvival proteins must be neutralized for apoptosis, Pro-survival Bcl-2 proteins restrain Bax and Bak, Apoptosis in the absence of "activator" BH3-only proteins, BH3-only proteins activate Bax and Bak indirectly, Control of Bak, Outstanding questions